Braudel revisited : the Mediterranean world, 1600-1800 - Ruiz, Teofilo F., 1943-; Symcox, Geoffrey; Piterberg, Gabriel, 1955- (Toronto [Ont.] : University of Toronto Press in association with the UCLA Center for Seventeenth- and Eighteenth-Century Studies and the William Andrews Clark Memorial Library, 2010)
"Fernand Braudel (1912-1985), was a leading French historian and author of, among other books, the groundbreaking The Mediterranean and the Mediterranean World in the Age of Philip II (1949). One of the founders of the Annales School in France, Braudel insisted on treating the Mediterranean region as a whole, irrespective of religious and national divides. Braudel's new historiography rejected political history as the dominant discipline and espoused a 'total history' or a 'history from below' that would tell the story of the vast majority of humanity hitherto excluded from the grand narrative. At the time of the book's appearance, this premise was revolutionary
The contributors to Braudel Revisited assess the impact of Braudel's work on today's academic world, in light of subsequent methodological shifts. Engaging with Braudel's texts as well as with his ideas, the essays in this volume speak to the enduring legacy of his work on the ongoing exploration of early modern history."--Pub. desc
The problem of unbelief in Braudel's Mediterranean -- Braudel and the Mediterranean city -- A Mediterranean culture of factions? Bilateral factionalism in the greater Mediterranean Region in the pre-modern era -- Polyglottism in the Ottoman Empire: a reconsideration -- Braudel's Eastern Mediterranean revisited -- Sebastianism in theory and practice in early modern Portugal -- Geneva by the sea: the Reformation in Nîmes in historiographical context -- The Algerian economy and Cervantes' first work of narrative fiction -- Braudel and the cultural history of the Mediterranean: anthropology and Les lieux d'histoire -- Il faut méditerraniser la musique after Braudel.
Includes bibliographical references and index.
Includes some text in Spanish.
Print version record.
eBooks on EBSCOhost
Keywords: Braudel, Fernand; Braudel, Fernand; Braudel, Fernand; Méditerranée et le monde méditerranéen à l'époque de Philippe II (Braudel, Fernand); Historiography; Historians -- France; Mediterranean Region -- History -- 1517-1789.; Mediterranean Region -- Civilization; Méditerranée, Région de la -- Histoire -- 1517-1789.; Méditerranée, Région de la -- Civilisation; Historiographie; historiography; HISTORY -- Historiography; HISTORY -- World; Civilization; Historians; Historiography; France; Mediterranean Region; 1517-1789; History